APPLICATION OF THE COPULA METHOD TO ANALYZE THE RELATIONSHIPS OF MACROECONOMIC FACTORS AFFECTING THE CSPI - Saleh, Sri Endang; Pakaya, Debyyansa; Hasan, Irsan K.; Djakaria, Ismail (PATTIMURA UNIVERSITY, 2023)
The Composite Stock Price Index (CSPI) is a valuable number in assessing the performance of the stocks listed on the stock exchange; by looking at the Composite Stock Price Index, investors can determine their investment strategy. However, the rise and fall of the Composite Stock Price Index depend on a country's macroeconomic conditions; if the economy weakens, the company's performance will also undermine investors' confidence, and confidence decreases. Analysing the relationship between the Composite Stock Price Index with macroeconomic factors can show how much the influence of these factors on the increase or decrease in the Composite Stock Price Index, the macroeconomic factors in question are inflation, interest rates and the rupiah exchange rate. In this study, dependency analysis was carried out with the Copula approach method involving the Tau Kendal method for parameter estimation and the Maximum Likelihood Estimation (MLE) method to choose the best Copula model to explain the relationship between the Composite Stock Price Index and these macroeconomic factors. Research results in it are found that the best Copula that can explain the dependency structure between the Composite Stock Price, The index with inflation and interest rates is the Gumbel Copula with parameters θ ̂= 1.264 and θ ̂= 1.174, While the Copula model is the best that can explain the structure of the dependency between Composite Stock Price Index and the exchange rate is Copula Student-t with parameter θ ̂= −0.6037.